Strengthening fegional surveillance and financial safety net mechanisms in Asia workshop highlights.
Strengthening Regional Surveillance and Financial Safety Net Mechanisms in Asia was a workshop that gathered policymakers, representatives from international organizations, and academics. It comprised panel discussions on crises lessons and crises response mechanisms as well as technical sessions on regional financial safety nets and new instruments of economic surveillance.